2014
DOI: 10.1080/00071668.2014.949622
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of water as a potential risk factor for cross-contamination withSalmonella, CampylobacterandListeriain a poultry abattoir

Abstract: Water used in a modern poultry processing line was tested from October 2005 to June 2006 to determine the level of bacteria in an abattoir in Germany. A total of 420 water samples were taken from 14 processing sites (PSs), at 10 times, and from three different hours of the working shift at three sampling hours (SHs) at 5:00 a.m. (SH 1), 9:00 a.m. (SH 2) and 12:00 a.m. (SH 3). Each sample was assessed for the aerobic plate count (APC) and the prevalence of Salmonella, Campylobacter, Listeria and Yersinia over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…These results highlighted that the use of water probably influenced in the obtained results, not assuring an adequate cleaning of the conveyor belts surfaces. The fact that water spread microorganisms (Hamidi et al, 2014) is worrying because psychrotrophic bacteria cause food spoilage and poultry meat had direct contact with the surface of conveyor belts previously to packaging.…”
Section: Mesophilicmentioning
confidence: 99%
See 2 more Smart Citations
“…These results highlighted that the use of water probably influenced in the obtained results, not assuring an adequate cleaning of the conveyor belts surfaces. The fact that water spread microorganisms (Hamidi et al, 2014) is worrying because psychrotrophic bacteria cause food spoilage and poultry meat had direct contact with the surface of conveyor belts previously to packaging.…”
Section: Mesophilicmentioning
confidence: 99%
“…In a previous study, Bersot et al (2012) suggested that this continuous cleaning with water is not necessary and its removal can reduce effluents discharge in reducing the environment. Furthermore, the water at every processing step can be a risk, requiring more attention to effective water management in the processing plan (Hamidi et al, 2014).…”
Section: Mesophilicmentioning
confidence: 99%
See 1 more Smart Citation
“…A maioria dos abatedouros-frigoríficos de aves são indústrias altamente automatizadas e, apesar dos avanços tecnológicos, a carne de frango ainda é passível de contaminação por Salmonella spp. A própria automatização do processo propicia a contaminação cruzada por meio do contato com a água contaminada nas etapas de escaldagem e resfriamento, disseminação da contaminação durante a depenagem e disseminação de resíduos gastrointestinais durante as várias etapas da evisceração (RASSCHAERT et al 2008;HAMIDI et al, 2014).…”
Section: Pontos Críticos De Contaminação Durante O Abate De Avesunclassified
“…na pele (LILLARD, 1989). Hamidi et al (2014) coletaram um total de 420 amostras de água em diferentes pontos de processamento, sendo que 46 amostras estavam contaminadas com Salmonella spp. Lillard (1989) demonstrou que após a imersão em água, cristas e fendas da pele se tornam mais pronunciadas, aprisionando as bactérias que inicialmente estavam em um filme de água sobre a pele, dificultando a ação de substâncias antimicrobianas.…”
Section: Pontos Críticos De Contaminação Durante O Abate De Avesunclassified